Learning through educational game: an experience with children, youth and adults with Down syndrome (Research, Society and Development, 2020)
Through various playful activities, the institution Vitória Down has been complementing the educational process of children, young people and adults with Down Syndrome (DS) in the state of Espírito Santo. The application of several educational games to students has been used in the literature as a source of learning and development for students with Down Syndrome. Therefore, taking the context of the institution Vitória Down as a reference, this study sought to observe and conduct the interaction of 10 students with DS through the application of the mobile game Dengue Zero in their teaching-learning process. Despite some difficulties in understanding and interpreting the “stages” of the game, the fact that students are constantly in contact with electronic equipment and use of the internet was crucial for these students to be successful in their teaching-learning process.